Learning Resources and Efficiency of Open Distance Learning Programmes in Kwara State, Nigeria: Adedapo Adetiba ATOLAGBE, Olubukola James OJO, Abdulrahman Sayuti OMOSIDI (PJDOL, 2023)
The Open Distance Learning (ODL) commenced in Nigeria in the year 2003 by the National Open University of Nigeria (NOUN) and many universities in the country have also adopted it. The study focused purposely on four ODL centers in Kwara state. Five research questions and three research hypotheses were formulated. The student sampleswere selected through convenience sampling method.